ANALISIS PERBANDINGAN STABILITAS SISTEM KEUANGAN BANK PEMERINTAH DAN BANK SWASTA DI INDONESIA DENGAN PENDEKATAN MIKROPRUDENSIAL - Ambardi Ambardi; Adi Rizfal Efriadi; Rizki Maulana Pribadi; Aam Aminah; Ahmad Eko Saputro (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to assess the stability of the financial system across state-owned and national private banks using a microprudential approach. Several important microprudential indicators used in this study include the Capital Adequacy Ratio (CAR), which measures a bank's ability to bear the risk of loss. Asset quality measures the quality of bank assets, including the Non-Performing Loan (NPL) ratio. Liquidity measures the bank's ability to meet its short-term obligations. Profitability measures the bank's ability to generate profits. Net Interest Margin (NIM) to measure the bank's efficiency in interest management. Operating Costs and Operating Income (BOPO) to measure the efficiency of the bank's operational costs.Methods: This research is a quantitative descriptive study. The sample used in this study consists of banks with assets ranked among the 10 largest in Indonesia. All 10 samples were determined using a purposive sampling technique. financial performance summaries for the 2022-2024 period. The variables examined in this study include credit quality (NPL), bank liquidity (LDR), capital adequacy (CAR), profit-generating capacity (ROA and NIM), regulatory compliance (Reserve Requirement), and management efficiency (BOPO). The data analysis technique used was descriptive statistical analysis, as well as the Independent Sample t-test to compare the averages of two unrelated groups.Results: From the difference test, only the Capital Adequacy Ratio (CAR) indicator has a significant difference between the government bank group and the private bank group, while for other indicators such as Return on Assets (ROA), Net interest margin (NIM), Operating Costs Operating Income (BOPO), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Reserve Requirement (RR) there is no significant difference between the government bank group and the private bank group. Keywords: Comparison, Financial Stability, Government Banks, Microprudential, Private Banks